Nursing diagnoses in the safety and protection domain in people with HIV/Aids - Juliana de Oliveira Faria; Girlene Alves da Silva (Universidade Federal de Goias, 2014)
Hospitalizations of individuals with HIV/Aids are a consequence of their vulnerability to falling ill. Knowing identified human responses is essential to the promotion of health care. The objective of this study was to identify the nursing diagnoses in the safety and protection domain from NANDA-I Taxonomy II in people with HIV/Aids in a hospital in the state of Minas Gerais, Brazil. This descriptive study was performed with 30 patients in the period between March and September of 2011. The diagnoses were identified and analyzed by Risner's model of diagnostic reasoning and descriptive statistics It was found that 100% of the participants presented diagnoses in the referred domain, thus reinforcing the vulnerability of the studied clientele. Thus, it is highlighted that prioritizing the identified diagnoses in nursing intervention plans is important, as well as focusing the identified conditions to strengthen health care actions. Descriptors: Nursing Care; Delivery of Health Care; Nursing Diagnosis; Acquired Immunodeficiency Syndrome.